Benzylation of Aromatic Compounds Catalyzed by 3-Methyl-1-sulfonic Acid Imidazolium Tetrachloroaluminate and Silica Sulfuric Acid under Mild Conditions - Zolfigol, Mohammad Ali; Vahedi, Hooshang; Azimi, Saeid; Moosavi-Zare, Ahmad Reza (Synlett, 2013)
In this work, efficient procedures for benzylation of a range of aromatic compounds by benzyl acetate in the presence of catalytic amounts of 3-methyl-1-sulfonic acid imidazolium tetrachloroaluminate ([Msim]AlCl4) or silica sulfuric acid (SSA) under mild conditions are described. Simple methodology, easy workup procedure, clean reaction and reusability of the catalyst are some advantages of this work.
Keywords: benzylation; benzyl acetate; 3-ethyl-1-sulfonic acid imidazolium tetrachloroaluminate; silica sulfuric acid